Recognizing and Verifying the Handwritten Fields on Cheques Using Filtering Techniques - M. R. Krishna Rao Veeranki; B.N.V.Praneeta; B. Gowthami; J.Tarun; M. Indu Sri (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
In general, bank cheques are used extensively for financial transactions in various organizations. Cheques are always verified manually. The traditional verification process will always include date, signature, legal information, and payment written on the cheques. In this paper, extracting the legal information from captured cheque image is obtained by preprocessing the image, extracting required information and then recognizing and verifying the handwritten fields. Image processing techniques like thinning, median filtering, dilation, and verification techniques are also employed in this approach.
Keywords: OCR; TESSERACT; OPENCV